Fair game : a complete book of soccer for women / Lorrie Fair with Mark Gola. - Fair, Lorrie (McGraw-Hill, 2003)
Women's soccer hero & Nike spokesperson Lorrie Fair offers her knowledge of the fundamental skills, playing tactics, training techniques & mental toughness which has helped her become a top professional.